Survival after breast cancer local recurrence according to therapeutic strategies. Issue 8 (August 2017) - Houvenaeghel, G.; Boher, J.M.; Michel, V.; Bannier, M.; Minsat, M.; Tallet, A.; Cohen, M.; Buttarelli, M.; Resbeut, M.; Lambaudie, E.
Abstract: Aims: To compare survival outcomes after mastectomy (Mt) and lumpectomy plus interstitial brachytherapy (LpIB) in the treatment of breast cancer local recurrence (LR) occurring after conservative surgery. Methods: Medical records of patients treated for an isolated LR from January 1, 1981 to December 31, 2009 were reviewed. To overcome the bias due to the fact that treatment choice (Mt or LpIB) was based on prognostic factors with LpIB proposed preferentially to women with good prognosis, Mt and LpIB populations were matched and compared with regard to overall survival (OS) and metastasis free survival (MFS). Results: Among 348 patients analyzed, 66.7% underwent Mt, 17.8% LpIB and 15.5% Lp alone. After a median follow-up of 73.3 months, 65 patients had died (42/232 Mt, 8/62 LpIB, 15/54 Lp). Before matching, OS and MFS at 5 years were significantly better in the LpIB compared to the Mt group, due to significantly more frequent poor prognostic factors in the latter (p = 0, 07 and p = 0, 09 respectively, log-rank significance limit of 10%). After matching, the benefits of LpIB disappeared since MFS and OS rates were not significantly different in both groups (p = 0.68 and 0.88 respectively). After LpIB, the second LR rate was 17% at 5 years and 30% at 10 years. Conclusion: A second conservative breast cancer treatment associating lumpectomy and interstitial brachytherapy is possible for selected patients with LR, without decrease in neither OS nor MFS compared to mastectomy.